Two new cryptic and sympatric species of the king crab parasite Briarosaccus (Cirripedia: Rhizocephala) in the North Pacific. (January 2016) - Noever, Christoph; Olson, Andrew; Glenner, Henrik
Abstract : Rhizocephalan barnacles have been reported to parasitize a wide range of king crab species (Lithodidae). So far all these parasites have been assigned to a single species, Briarosaccus callosus Boschma, 1930, which is assumed to have a global distribution. Here we investigate Briarosaccus specimens from three different king crab hosts from the fjord systems of Southeastern Alaska: Lithodes aequispinus Benedict, 1895, Paralithodes camtschaticus (Tilesius, 1815), and Paralithodes platypus (Brandt, 1850). Using molecular markers and by morphological comparison we show that Briarosaccus specimens from these three commercial exploited king crabs are in fact morphologically distinct from B. callosus, and further represent two separate species which we describe. The two new species, Briarosaccus auratum n. sp. and B. regalis n. sp., are cryptic by morphological means and were identified as distinct species by the use of genetic markers (COI and 16S). They occur sympatrically, yet no overlap in king crab hosts occurs, with B. auratum n. sp. only found on L. aequispinus, and B. regalis n. sp. as parasite of the two Paralithodes hosts. © 2015 The Authors. Zoological Journal of the Linnean Society published by John Wiley & Sons Ltd on behalf of The Linnean Society of London